Using Their (Photo)Voice: Student Experiences with Nature-Based Physical Activities In and Beyond Physical and Health Education - Gruno, Jennifer; Gibbons, Sandra (The Canadian Journal of Action Research)

(untitled) (Canadian Association of Action Research in Education, 2024)
This study employed a participatory action research methodology, Photovoice, to explore the experiences of adolescent students while learning nature-based physical activity (NBPA) in, and beyond, Physical and Health Education (PHE). Students were asked to take photos both within PHE lessons and outside of school, and write captions to analyze their photos, as part of a unit entitled NBPA in Pictures. Findings indicated that through the NBPA in Pictures unit in PHE, students were able to: connect to both place and others within PHE and outside of school; overcome challenges to being active in nature; describe nature’s impact on their body and being; and, gain the desire to inspire others to enjoy nature.